Sistem Informasi Penanganan Keluhan Warga Desa Bebasis Website (Studi Kasus Pemerintahan Desa Gunung Jati) - Tetra Andiko Iwari; Nyimas Sopiah (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2022)
Gunung Jati Village is a village located in Cempaka District, East Ogan Komering Ulu Regency. The Gunung Jati Village Government opened a complaint handling service to serve complaints from Gunung Jati Village residents against services from the village government. However, the lack of maximum complaint handling services causes complaints from villagers not to be recorded properly. Based on these problems, an instrument supported by an information system is needed, by developing an information system for handling village residents' complaints. Information system development is carried out by modeling business processes, requirements analysis, designing and implementing an information system for handling complaints from villagers by applying an object-oriented approach. The result of this research is that a web-based village complaint handling information system can help the complaints of government villagers in Gunung Jati village, and also make it easier for village communities to get information or other complaints in Gunung Jati village. Keywords: information system, complaint handling, Gunung Jati village.